Lachancea thermotolerans as an alternative yeast for the production of beer†. Issue 4 (16th November 2016) - Domizio, P.; House, J. F.; Joseph, C. M. L.; Bisson, L. F.; Bamforth, C. W.
Abstract : The ability of Lachancea thermotolerans strains to ferment brewer's wort has been investigated. Initial fermentations with three L. thermotolerans strains compared the use of maltose and maltotriose, as well as production of glycerol and lactic acid and pH evolution over the course of the fermentation. The most promising strain was subsequently tested for additional traits important for beer production, including pitching rate, generational capacity, foam stability, hop tolerance, vicinal diketone production, oxygen requirement and flocculation. These tests suggest that L. thermotolerans may be a good choice for producing sour beers in a single fermentation step without the use of lactic acid bacteria. Copyright © 2016 The Institute of Brewing & Distilling